Contributions of loneliness to cognitive impairment and dementia in older adults are independent of other risk factors and Alzheimer’s pathology: a narrative review - Oken, Barry S.; Kaplan, Josh; Klee, Daniel; Gallegos, Autumn M. (Frontiers in Human Neuroscience, 2024)
beyond social isolation. Loneliness needs to be assessed in all studies of cognitive decline in elders, since it significantly contributes to the variance of cognitive function. It will be useful to better define the underlying mechanism of loneliness effects on cognition to determine if it is similar to other psychological factors related to excessive stress reactivity, such as neuroticism or even depression, which are also associated with cognitive decline. It is important from a health perspective to develop better strategies to decrease loneliness in older adults.